Pengaruh Kondisi Financial Distress terhadap Penerimaan Opini Audit Going Concern dengan Good Corporate Governance sebagai Variabel Pemoderasi - Vania Tyas Utami; Abriandi Abriandi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2018)
This research aims to test the effect of financial distress condition towards acceptance of going concern audit opinion and good corporate governance as moderating relationship between financial distress condition towards acceptance of going concern audit opinion. The sample selection using purposive sampling of manufacturing companies listed in IDX in 2010-2015. The analytical method using logistic regression and MRA. Test results showed financial distress condition affect negatively to acceptance of going concern audit opinion. Good corporate governance as measured by managerial ownership was able to weaken connection between financial distress condition towards acceptance of going concern audit opinion, whereas proportion of independent board commissioners, institutional ownership, and audit committee not being able to moderate relationship between financial distress condition towards acceptance of going concern audit opinion.